THE DEVELOPMENT OF ISLAM IN THE KUBU KINGDOM (1768 – 1944) - Erwin Mahrus (Al-Albab, 2012)
The origin of the Kubu Kingdom was previously marked with the establishment of a village at the junction of three rivers and the construction of a fort in 1768. In other words, Kubu was a checkpoint to secure the waters from pirate attacks (Djunaidy, 2001). The new village was officially named “Kubu” in 1775 (Yosep, 1995). Later on, it became a kingdom because of the massive migration into the new territory. They embraced Islam and made it an Islamic Kingdom in West Borneo. The territory of Kubu Kingdom was very limited merely to include Padang Tikar, Terentang, Kubu, and Teluk Pekadai. Originally this area was empty. It means that the Kubu Kingdom initially did not consist of densely populated villages. As a new region, it is thought that the establishment of this Kingdom coincided with the advent of Islam brought by Syarif Idrus Alaydrus. Thus, there have been long dynamics of Islamization in this Kingdom, and reached its peak when Syarif Abbas was in power. During his reign, the institution of the mufti was created and a number of religious works were written. This paper looks at the process of early entry and development of Islam in the Kubu Kingdom, its religious scholars and their works as well as its religious institutions that once existed in the Kingdom. Keywords: Islam, Kubu Kingdom, religious works and religious institutions